The characterisation of dendritic cell, microglial, macrophage and T cell responses during mycobacterial infection of the central nervous system - Kgoadi, Khanyisile (Department of Clinical Laboratory Sciences, 2022)
Background: Tuberculosis (TB) remains a global health challenge and a quarter of the global population is infected with latent TB. It is a single infection that causes most deaths and was the number one cause of death in South Africa in 2017. Bacille Calmette-Guerin (BCG) remains the only licensed vaccine for protection against TB. Although TB primarily occurs as a pulmonary infection after inhalation of Mycobacterium tuberculosis (M. tuberculosis) bacilli, it can disseminate to other organs causing extra-pulmonary TB (EPTB). Approximately 5-15% of EPTB cases are attributed to central nervous system tuberculosis (CNS-TB) which commonly manifests as TB meningitis. CNS-TB is a severe form of TB associated with high morbidity and about 50% mortality due to inconclusive diagnosis and treatment challenges. Children and immunocompromised adults like those coinfected with HIV/AIDS are higher risk groups for the development of CNS-TB. Pathogenesis of CNS-TB occurs as a secondary infection during haematogenous dissemination of pulmonary TB to the brain parenchyma and meninges where inflammation occurs after rupture of rich foci into the subarachnoid space. Mechanisms by which M. tuberculosis infects the CNS and specific cell types targeted are not fully characterized. Little is understood of the cells that regulate CNS-TB, their respective functions, their cellular interactions, and contributions to the overall protection of the CNS. Most studies have focussed on microglia and macrophages as the preferential targeted antigen-presenting cells (APCs) by M. tuberculosis and neglected dendritic cells (DCs) to an extent because no consensus had been reached regarding the presence of DCs in a healthy CNS. Both myeloid (APCs) and T cells contribute to protection against CNS-TB. This study characterized the dendritic cell, microglial, macrophage, and T cell responses during mycobacterial infection of the CNS. We also investigated the modulation of T cells by DCs during CNS-TB. Methodology and Results: Wild-type female C57BL/6J mice were intracerebrally (i.c.) infected with M. tuberculosis H37Rv or Mycobacterium bovis BCG while control animals were saline inoculated and naive mice. Mice were euthanized at weeks 2, 4, 6, and organs harvested for experimental analysis. Histology results detected acid-fast bacilli using Ziehl-Neelsen (ZN) stain in the brains of M. tuberculosis and BCG i.c. infected mice, respectively. This was accompanied by a high degree of inflammatory responses in the brain ventricles and meninges of infected mice as compared to saline control mice shown by Hematoxylin and Eosin (H & E) staining. Although controlled brain bacterial burdens were demonstrated from homogenates of M. tuberculosis or BCG infected mice, dissemination to the spleen and lungs occurred. The histopathological results showed the successful reproduction of the murine CNS-TB infection model. For immunophenotyping, flow cytometry analysis of single-cell suspensions generated from brains and cervical lymph nodes were characterized for phenotypic and functional profiles. We detected the recruitment of macrophages and DCs to the brain from the periphery and an expansion of brain APCs (microglia, brain infiltrating macrophages, and DCs) during mycobacterial infection of the CNS. Brain APCs from infected animals displayed highly activated and mature phenotypes as shown by increased numbers of these cells expressing MHCII, co-stimulatory CD86 molecule, pro-inflammatory cytokines (IFNg, TNFa, IL-1b, IL-6, IL-12) and an anti-inflammatory cytokine (IL-10) in comparison to saline control mice. We also demonstrated preferential recruitment of mature conventional DCs (CD11c+, MHCII+) that express chemokine receptor-7 (CCR7) to the brain and cervical lymph nodes (CLNs), a phenomenon that may have contributed to the recruitment and expansion of predominantly effector CD4+ T cells than CD8+ T cells (CD44+CD62L-) to the brain and CLNs during mycobacterial infection of the CNS. Increased numbers of recruited CD4+ T cells and CD8+ T cells expressed T-bet [T-helper (Th1) transcription factor) in the brain and CLNs post-infection. At week 4 post intracerebral infection, increased numbers of these T cells expressed both T-bet and FoxP3 (regulatory transcription factor) during CNS-TB and identified a higher frequency of polyfunctional IFNg+TGF-b+CD4+ T cells than IFNg+TGF-b+IL-10+CD4+ T cells. M. tuberculosis-infected DCs from CLNs of CNS-TB mice were cocultured with naïve CD3+ T cells to generate a DC-T cell coculture, cells were sorted using fluorescence-activated cell sorting (FACS). DC-T cell coculture demonstrated increased percentage expression of IFNg, IL-4, IL-10 and TGF-b responses by CD4+ T cells and CD8+ T cells during CNS-TB. Our in vitro coculture findings validated in vivo findings of recruited brain CD4+ T cell cytokine responses that showed a combination of Th1 and regulatory T cell immune responses. Conclusion: We successfully reproduced the CNS-TB murine model, which proved valuable in studying immune responses. The functional mature phenotypes of detected brain APCs (microglia, brain infiltrating macrophages, DCs) suggest their capabilities of inducing antigen-specific T cell responses that contributed to initiating and mediating immunity during mycobacterial infection of the CNS. Our study findings suggest protection against mycobacterial infection of the CNS was achieved by characterized cells based on reduced brain bacterial burdens and 100% animal survival rate. Detrimental disease outcome was prevented by the balance achieved between proinflammatory and anti-inflammatory responses. The novel mechanism employed by conventional DCs during CNS-TB is modulating CD4+ and CD8+ T cell cytokine responses to Th1 and Treg polarization that achieved M. tuberculosis control in the brain. We demonstrated that DCs can be targeted for strategic therapeutic intervention against CNS-TB. Therefore; we support ongoing research that focuses on DCs for the development of tuberculosis vaccines and host-directed therapy. This study provided new knowledge on immune mechanisms and pathogenesis experienced during TBM, thus adding to the current gap of advancing basic and translational TBM research that will inform clinical interventions. These new insights have the potential to help reduce the high death and disability associated with CNS-TB.